PENINGKATAN KEMAMPUAN PENALARAN STATISTIS MAHASISWA MELALUI PEMBELAJARAN BERBASIS PROYEK BERBANTUAN ICT - Karman La Nani; Marwia Tamrin Bakar; Soleman Saidi (EDUKASI, 2020)
The problem with this research is the students’ low ability of statistical reasoning. This study aims to determine the students’ achievement and improvement of statical reasoning through project-based learning with ICT assistance. This research was in the form of a quasi-experimental design of the pretest-posttest control group. The numbers of samples of this study were 51 students taken by purposive sampling from 102 students who took statistics introductory lectures. This study has two variables, namely: the application of project-based learning with ICT assisted as an independent variable, and the students' statistical reasoning ability as an independent variable. The instrument used for data collection was six items of an essay the statistical reasoning test. The data obtained were analyzed descriptively and inferentially. Descriptive analysis, including a description of student statistical reasoning achievement and improvement. The inferential analysis is using the Mann-Whitney U test statistic. The results showed that the students’statistical reasoning achievement and improvement who received project-based learning with ICT assisted was better than those who obtained conventional learning. Students’ statistical reasoning Achievement who received project-based learning with ICT assisted in the good category while those who received conventional learning in the sufficient category. The increased student's statistical reasoning who received project-based learning with ICT assisted was relatively high and those who received conventional learning where classified as moderate. There is a significant difference in the achievement and improvement of students' statistical reasoning abilities between those who obtain project-based learning with ICT assisted and those who obtain conventional learning. The significance of these differences can be concluded that the implementation of project-based learning with ICT assisted can improve students' statistical reasoning abilities.